2016
DOI: 10.1093/humrep/dew329
|View full text |Cite|
|
Sign up to set email alerts
|

Overweight and obese but not normal weight women with PCOS are at increased risk of Type 2 diabetes mellitus—a prospective, population-based cohort study

Abstract: STUDY QUESTION: What are the respective roles of polycystic ovary syndrome (PCOS), long-term weight gain and obesity for the development of prediabetes or Type 2 diabetes mellitus (T2DM) by age 46 years? SUMMARY ANSWER: The risk of T2DM in women with PCOS is mainly due to overweight and obesity, although these two factors have a synergistic effect on the development of T2DM.WHAT IS KNOWN ALREADY: PCOS is associated with an increased risk of prediabetes and T2DM. However, the respective roles of PCOS per se and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
65
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(80 citation statements)
references
References 33 publications
(57 reference statements)
11
65
0
4
Order By: Relevance
“…In the present study, PCOS women without GDM were significantly leaner than women with GDM, and their mean BMI was similar to the BMI of the controls, which may explain the findings. This result is also in keeping with the findings of a recent large Finnish cohort study in which only overweight and obese women with PCOS were at risk for subsequent T2D ( 31 ). These results suggest that obese women with PCOS are at substantial risk for GDM and should, therefore, be recognised and counselled as a high-risk group before or during the early stages of pregnancy to achieve more efficient therapeutic interventions.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, PCOS women without GDM were significantly leaner than women with GDM, and their mean BMI was similar to the BMI of the controls, which may explain the findings. This result is also in keeping with the findings of a recent large Finnish cohort study in which only overweight and obese women with PCOS were at risk for subsequent T2D ( 31 ). These results suggest that obese women with PCOS are at substantial risk for GDM and should, therefore, be recognised and counselled as a high-risk group before or during the early stages of pregnancy to achieve more efficient therapeutic interventions.…”
Section: Discussionsupporting
confidence: 90%
“…The results of our study confirm a high risk of abnormal glucose tolerance in overweight/obese women with diagnosed PCOS [ 51 ]. The recently published data from the multi-centre national population health examination survey (WOBASZ) revealed that the prevalence of IFG in the cohort of Polish women aged 20–34 years totals 4.3%, which is much lower than in our PCOS cohort (25.8%) [ 52 ].…”
Section: Discussionsupporting
confidence: 82%
“…If insulin resistance is accentuated among obese PCOS women, these women should be at a greater risk of developing type 2 diabetes. Available data support this connection [ 39 , 40 ]. However, in the DHS, the average glucose levels and percentage of women with fasting glucose levels >100 mg/dL were not increased in PCOS women.…”
Section: Discussionmentioning
confidence: 88%